Pengaruh Dukungan Suami Terhadap Pemilihan Metode Kontrasepsi di Puskesmas Rawat Inap Kedaton Bandar Lampung - Sharlene Sabrina; Rodiani (CV. Jasa Sukses Abadi, 2022)
The population growth rate in the city of Bandar Lampung for the 2002-2010 period was 1.61%, in the 2010-2015 period it increased to 2.04. One way to overcome this problem is the family planning program. The results of the 2017 Indonesian Demographic and Health Survey (IDHS) show that people still use a lot of short-term contraceptives, even though short-term contraceptives have a high risk of failure. This is evidenced by the data on the percentage of MKJP and non-MKJP users at Kedaton Health Center, which is 0.08% while non-MKJP users are 0.92%. Husband's support is one of the external factors in the choice of contraceptives which become an amplifier to influence someone's behavior. Much information states that the decision was obtained from the wife because of the husband's interference. This study aims to determine the effect of husband's support on the choice of contraceptive methods at the Kedaton Inpatient Public Health Center in Bandar Lampung. This research is an observational analytic study with cross sectional design with a measuring instrument in the form of a questionnaire and with the research subjects as many as 109 respondents, taken by consecutive sampling method. The results of this study were processed using computer software with the Chi-square test method. The results obtained showed that there was a statistically significant relationship between the influence of husband's support on the choice of contraceptive methods at the Kedaton Inpatient Public Health Center in Bandar Lampung (p = 0.02).